(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
Trichinellosis in a zoonotic parasitism of worldwide distribution caused by nematodes of the genus Trichinella. Argentina is considered an endemic country for this zoonosis and so far four species have been identified, spiralis, patagoniensis, britovi and pseudospiralis. It can affect both domestic animals such as pigs, dogs, horses, or wild animals such as cougars, armadillos, wild boars, and wild pigs. With the aim of knowing if any species of Trichinella circulates among the wild fauna of the province of Santa Fe, 22 samples of muscle from pigs between wild and wild boars were analyzed by Artificial Digestion, five from aguará guazú (Chrysocyon brachiurus), one of cat wild (Leopardus geoffroyi), one of weasel (Didelphis albiventris) and one of an equine (Equus caballus). All samples were negative.